Effects of Companies’ Initiatives to Reduce Early Retirement Among Older Workers - Midtsundstad, Tove; Hermansen, Åsmund; Nielsen, Roy A. (Nordic Journal of Working Life Studies, 2012)
Although active ageing policy and practice vary between countries, we believe that knowledge about the effects of Norwegian companies’ initiatives to delay early retirement is of interest for all countries striving to increase the employment rates of older workers. Since the agreement on a more inclusive working life (IW agreement) was signed in 2001, the Norwegian government and social partners have encouraged companies to develop a more senior-friendly policy and implement special measures to retain older workers. In this article, we evaluate the effects of such measures. Our research question is, have preventive measures offered by companies to employees aged 62 years and older contributed to reduced rates of early retirement? We use a ‘difference-in-differences’ approach and examine whether measures at the company level to counteract early retirement actually affect older employees’ retirement decisions, controlling for different individual and enterprise factors. This is done by comparing changes and differences in the individual likelihood of early retirement on the contractual pension (AFP scheme) and disability pension in the period 2002–2007 among employees 62 years of age in businesses with and without the corresponding preventive measures/instruments. The analyses show that the likelihood that a 62-year-old worker will retire on the AFP scheme has increased from 2002 to 2007. This applies equally to 62-year-old employees in enterprises that have enacted special measures to retain older workers as well as 62-year-olds in enterprises that have not enacted any such measures. On the other hand, the likelihood that a 62-year-old worker will retire because of disability decreased from 2002 to 2007, among employees in both the intervention enterprises and the control enterprises. However, when controlling for other relevant characteristics of individuals and enterprises, the analysis indicates that the measures as such have had no effect on the likelihood of 62-year-olds retiring.